Konstruksi Realitas Media Hiburan: Analisis Framing Program Redaksiana Di Trans7 - Prawira, Indra (Humaniora, 2014)
News program is one of Indonesia's most popular programs although in practice the program is still unable to compete with entertainment programs. Redaksiana program has successfully captured the heart of Indonesian audiences with achieving a high rating. This program displays different information to the news program in general, so it is more interesting to watch. Similar to other media, television program Redaksiana on Trans7 presents the news as the result of selection, construction, and reconstruction. Research problem studied is how Redaksiana constructs the news and what frames it uses. This research was conducted using qualitative method through the Pan and Kosicky framing model analysis. The structure of news framing elements studied was schematic, script, thematic, and rhetorical. The results were seen from the schematic structure and news scripts “Lose in votes, Legislator Candidate Blocked the Village Road” according to the script writing television news. Redaksiana featured the elements of 5Ws + 1H as the main element of the news. However, the frame was clearly visible in thematic and rhetorical. The way Redaksiana wrote the fact (thematic) and how Redaksiana emphasized the fact (rhetorical) of news writing indulge sensational elements. It is then pointed out as a factor that makes the news “Lose in votes, Legislator Candidate Blocked the Village Road” interesting to watch.